Performance of the traditional pooled variance t-test against the bootstrap procedure of difference between sample means - Teh, Sin Yin; Md Yusof, Zahayu; Yaacob, Che Rohani; Othman, Abdul Rahman (Universiti Putra Malaysia, 2010)
In this study, two methods of comparing the means of two samples were conducted.The first method used the traditional pooled variance t-test while the second method used the bootstrap method of comparing means.In the second method, pseudo sampling distributions were generated for the normal and non-normal distributions.For the non-normal we used the 23χ and a g=.5, h=.5 distribution. Group sizes {5, 15} and {15, 25} with equal and unequal variances were generated and for each method Type I error rates were evaluated.We found that about 20% and 33% of the study conditions using the pooled variance t-test were robust when group sizes are {5, 15} and {15, 25}, respectively.Whereas, about 33% and 47% of the study conditions in bootstrapped procedure were robust when group sizes are {5, 15} and {15, 25}, respectively.